Kenotic ecclesiology : select writings of Donald M. MacKinnon - MacKinnon, Donald M. (Donald MacKenzie), 1913-1994.; McDowell, John C.; Kirkland, Scott; Moyse, Ashley John, 1977- (Minneapolis Fortress Press, 2016)
"In this collection, MacKinnon's central writings on the major themes of ecclesiology, and especially the relationship of the church to theology, are gathered in one source. The volume features several of MacKinnon's important early texts. These include two short books published in the Signposts series during World War II and a collection of later essays entitled The Stripping of the Altars."--Cover.
Includes bibliographical references and index.
"Select bibliography of MacKinnon's works": pages 239-241.
Keywords: Philosophical theology; Philosophical theology